(eim) أثر سلوكيات القيادة التحويلية على إدارة المشاريع: دراسة حالة مؤسسة الصناعات الحديدية تبسة - عبداللاوي, عقبة; طبيب, عبد السلام (جامعة الوادي - University of Eloued, 2017)
تهدف هذه الدراسة إلى إبراز أثر سلوكيات القيادة التحويلية على إدارة المشاريع في مؤسسة الصناعات الحديدية (EIM) بمدينة تبسة (الجزائر). تم سحب عينة عشوائية بسيطة من هذه المؤسسة بلغ عددها 50 عامل (إداريين وعمال في مشاريع المؤسسة)، حيث وزّعت عليهم 50 استمارة استرد منها 43 استمارة قابلة للدراسة باستخدام الرزمة الإحصائية للعلوم الاجتماعية (SPSS) لتحليل البيانات. توصلت الدراسة إلى جملة من النتائج، أهمها وجود أثر لسلوكيات القيادة التحويلية على إدارة المشاريع، وهذه الأخيرة تفسر ما مقداره (54.4%) من التغير الحاصل في إدارة المشاريع. أوصت كذلك الدراسة بضرورة العمل على تعزيز أبعاد وسلوكيات القيادة ِالتحويلية في البيئة التنظيمية للمؤسسة، والارتقاء بهذه السلوكيات إلى المستويات العليا المرغوب بها لما لها من أثر على إدارة المشاريع This study aims to highlight the impact of transformational leadership behaviors on the management of projects at the level of the Metal Industries Enterprise (EIM) of Tebessa (Algeria). A simple random sample was drawn from the latter; It had 50 employees (administrative and workers in the company's projects). 43 recovered (out of 50 distributed) questionnaires were processed using the Social Science Statistics Package (SPSS). The study resulted in a number of results, including a strong correlation between transformational leadership behaviors and project management. These behaviors justify nearly 54.4% of the changes likely to occur in project management. The study also found the need to strengthen the dimensions and behaviors of transformational leadership in the organizational environment of the company and to promote those behaviors at higher levels desired due to their impact on project management.
The Impact of transformational leadership behaviors on project Case study of the Iron Industries Corporation (EIM) – Tebessa
مقال بمجلة الدراسات المالية والمحاسبية . مج 08 ع01. جوان 2017 . جامعة الوادي
Keywords: القيادة التحويلية، سلوكيات القيادة التحويلية، إدارة المشاريع